Dialectical materialism and teaching by words and deeds applied to the education of clinical medical students - Li, Meng; Sorayyaei Azar, Ali (Frontiers in medicine, 2023)
[...]Hoffert MM designed an original teacher development program that is closer to clinical practice than basic educational theory. Due to our lack of raw data, the statistical analysis suggested above could not be conducted. [...]we suggest that the authors use gender as the grouping basis, mark cases that mention “empathy” as positive and those that do not mention “empathy” as negative, perform a group t-test, and supplement the t-value and p-value. A training clinician's recall impression of a medical student may determine their overall evaluation of the student due to recall bias, and thus, there may be a deviation between the result and the true value.